Early career academics' understanding of library language: A study in a university setting in Bangladesh. Issue 3 (11th September 2019) - Yesmin, Shamima; Ahmed, S.M. Zabed
Abstract : Purpose: The purpose of this paper is to empirically examine the understanding of library terminologies by early career faculty members in a newly established rural university setting at the south coast of Bangladesh. Design/methodology/approach: A campus-wide survey was conducted using a structured questionnaire consisted of demographic questions and 35 multiple-choice questions on library terminologies. The multiple-choice questions asked faculty members to select the correct answer from a set of five answers. Findings: The findings indicate that early career university teachers lack adequate understanding of library terms; in fact, many of them either gave incorrect answers or was unsure about the term. It was found that faculty members had relatively better understandings of commonly used library terminologies, but they had real difficulties comprehending computer and technology-related terms. Significant differences were observed for some of the terms in case of their age, designation and teaching experience. Originality/value: This current study is unique in two ways: first, this is the first time an effort has been made to empirically examine the understanding of library terminologies by early career faculty members; and second, this study was conducted at a university in Bangladesh where the first language is not English.